The role of Azopolymer/Dendrimer layer-by-layer film architecture in photoinduced birefringence and the formation of surface-relief gratings - dos Santos, David S Jr (Langmuir : the ACS journal of surfaces and colloids, 2006)
The fabrication of nanostructured layer-by-layer (LbL) films strives for molecular control of the film properties directly connected with modifications in the film architecture. In the present report, the photoinduced birefringence and formation of the surface-relief gratings in LbL films obtained with an azopolymer (PS119) are shown to be strongly affected by the generation of the dendrimer employed in the alternating layers. Stronger adsorption of PS119 occurred when polypropylenimine tetrahexacontaamine dendrimer (DAB) of higher generations is used, due to a larger number of sites available to interact with azochromophores in PS119. In contrast, the photoinduced birefringence for LbL films made with the generation 1 dendrimer (DABG1) was higher, which can be explained by weaker interactions between adjacent layers. Strong interactions in LbL films consisting of PS119 and generation 3 or 5 dendrimers restrict the chromophore mobility, leading to a smaller birefringence. The interpretation is supported by the fact that surface-relief gratings with larger amplitudes were obtained for 35-bilayer films of DABG1/PS119 (31 nm) in comparison with films from DABG5/PS119 (5 nm). These gratings were formed with mass transport arising from a light-driven mechanism, as photoinscription was successful only with p-polarized light and not with s-polarized light